1997
DOI: 10.1055/s-0038-1665446
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Factor V (1691 G → A) Mutation in Turkish Population

Abstract: Frequency of Foclor V (1691 G-A) Mutotion in Turkish Populotion Dear Sir, A mutation in the Factor V gene (1691G-+ A in exon 10) was identified that formed the molecular explanation for the phenotype of APC-resistance in the large majority of affected individuals (1). This mutation, which is associated with a significant increase in tluombotic risk, has been found in 30-5070 of selected families with thrombophilia and in 20Vo of consecutive patients with venous tluombosis (2,3).The prevalence of the FV: Q506 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
68
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 0 publications
9
68
4
Order By: Relevance
“…This difference might be explained by the high prevalence of FVL in the Turkish population is higher than in the Western population (9.8% in Turkish Anatolian) [8].The high frequency of FVL in our cancer patients with TE was associated with its high prevalence among the normal Turkish population. Based upon our results, screening for FVL should be considered in cancer patients with an increased prevalence of TE.…”
Section: Letters To the Editor 1323mentioning
confidence: 59%
“…This difference might be explained by the high prevalence of FVL in the Turkish population is higher than in the Western population (9.8% in Turkish Anatolian) [8].The high frequency of FVL in our cancer patients with TE was associated with its high prevalence among the normal Turkish population. Based upon our results, screening for FVL should be considered in cancer patients with an increased prevalence of TE.…”
Section: Letters To the Editor 1323mentioning
confidence: 59%
“…Autosomal dominant factor V Leiden mutation is observed in 7% of the European population, whereas in 4.5-7.1% of the Turkish population (10,11). However, in another study, the prevalence of factor V Leiden mutation in Turkey was reported as 10% (12). Factor V Leiden was detected in 11-29% of patients with VTE.…”
Section: Discussionmentioning
confidence: 92%
“…Protein C, protein S, ATIII, and factor VIII levels were in the normal range. Our previous population study 3 had revealed that factor V Leiden heterozygosity was 9.8% with an allelic frequency of 4.9 which is one of the highest in the Western population. Prothrombin gene 20210 G-A heterozygosity was also found to be 2.7% in the Turkish population.…”
Section: Factor V Leiden Mutation As a Predisposing Factor For Veno-omentioning
confidence: 97%
“…Genetic analyses were performed as previously described. 3,4 In this ongoing prospective study, 10 consecutive children who received allogeneic BMT were included. The underlying diseases were as follows: AML (n = 5), juvenile myelomonocytic leukemia (n = 1), ␤-thalassemia major (n = 2), SAA (n = 1), Fanconi's anemia (FA; n = 1).…”
Section: Factor V Leiden Mutation As a Predisposing Factor For Veno-omentioning
confidence: 99%
See 1 more Smart Citation